Justicia restaurativa como garantía del principio de mínima intervención penal en el delito de defraudación tributaria - Monroy Chávez, Zulia Beatríz (2020)
Tax fraud corresponds to any manifestation of deception that the taxpayer carries out for his own benefit or that of a third party, in order to stop paying all or part of the taxes owed. The unjust tax penalty, although it constitutes a crime that would affect the state's collection power, it is necessary to prove reliably that it not only deceived the tax administration, but that it harmed it financially to obtain a benefit for itself or for another. This nexus of deception and monetary damage are the axes that complement the possible criminal behaviors of a person, restorative justice in cases of tax fraud crimes would not have as its purpose the disappearance of the punitive power of the State; Rather, it seeks to protect the right of the victim and the alleged perpetrator, combining the damage caused, in this case, through the tax administrative mechanisms, tax obligations can be enforced, and sanctions may be applied to the taxpayer……..